Design and Fabrication of a Microstrip Low-Pass Filter with a Wide Stopband Using a Windmill-Shaped Resonator - Roshani, Sobhan; Yahya, Salah I.; Khazaei, Shahram; Roshani, Saeed; Karami, Babak (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
In this paper, a microstrip low-pass filter (LPF) with a wide stopband and a sharp transition band is presented using a windmill-shaped resonator. Traditional LPF designs often face challenges such as narrow stopbands, high insertion loss, and large physical sizes, which limit their performance in modern communication systems. To address these challenges, the proposed filter exhibits low insertion loss, a sharp response in the transition band, a wide stopband, and a compact size. The windmill-shaped resonator is applied to achieve a sharp response in the transition band, while two suppressor cells are added to extend the stopband. The filter has a 3 dB cutoff frequency (fc) of 1.61 GHz, with an S12 parameter value of −20 dB at 1.7 GHz, resulting in a narrow transition band of 0.18 GHz, demonstrating its superior performance. In addition, the filter achieves a wide stopband that extends from 1.79 GHz to 11.26 GHz (a bandwidth of 9.47 GHz) with high attenuation. The physical size of the filter is 13.34 mm × 12.78 mm (0.097λ × 0.093λ). Overall, the proposed filter demonstrates excellent characteristics in both the passband and stopband regions, providing an effective solution for modern communication system requirements. The presented design effectively addresses key limitations in traditional LPF configurations, offering improved performance and compactness.